Prioritas Pengembangan Infrastruktur Agropolitan Berdasarkan Persepsi Petani: Analisis Importance–Performance di Kawasan Strategis Produksi Padi Babulu - Maryo Inri Pratama; Aditya Alif Hidayat; Rahmat Aris Pratomo; Umar Mustofa; M Gilang Indra Mardika (SPECTA Journal of Technology, 2026)
Babulu District is recognized as the primary rice-growing area in the region of North Penajam Paser Regency. This region is expected to become a food security buffer for the prospective Indonesian capital city (IKN). In spite of the significance and high agricultural potential of the region, agropolitan development in the region is limited by the lack of adequate infrastructures. This study aims to measure the significance levels and performance levels of agropolitan infrastructures in the region of Babulu District through the Importance-Performance Analysis (IPA) tool. Questionnaires and in-depth interviews with farmer groups and key informants are employed as data collection instruments. The findings revealed that irrigation channels and water reservoirs have the largest gaps in terms of importance-performance. This is followed by farm roads, storage facilities, and processing facilities. In contrast, electricity networks, markets, fertilizer kiosks, and extension centers have relatively higher performance levels in comparison to their significance levels. This suggests that a priority should be given to the development of primary infrastructures in agropolitan development in the region